A New Stability Indicating RP-HPLC Method for the Quantification of Trifluridine Using an Ion Pairing Agent - Annapurna, Dr. Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Trifluridine is a trifluoro thymidine derivative used to treat viral infections of eyes. A new stability indicating reversed-phase high-performance liquid chromatography (HPLC) method was developed and validated for the determination of trifluridine in pharmaceutical dosage forms (ophthalmic solution). Materials and Methods: Shimadzu Model CBM-20A/20 Alite HPLC system with PDA detector and Agilent C18column were used for the present study. Mobile phase mixture consisting of tetra butyl ammonium hydrogen sulfate and methanolin the ratio 48: 52, v/v with a flow rate 1.0 mL/min was chosen for the chromatographic elution of Trifluridine (Detection wavelength 265 nm). Results and Discussion: The method was linear over the concentration range 0.1–100 mg/ml with linear regression equation, y = 43421× + 2389.5 (R² = 0.9999). The limit of quantitation and limit of detection were found to be 0.0971 mg/ml and 0.0311, respectively. Stress degradation studies were performed and the method was validated as per ICH guidelines. Conclusion: The proposed RP-HPLC method is simple, precise, robust, accurate and can be applied for the routine analysis of Trifluridine dosage forms.